Energy Balance and Risk of Mortality in Spanish Older Adults - Camille Lassale; Álvaro Hernáez; Estefanía Toledo; Olga Castañer; José V Sorlí; Jordi Salas-Salvadó; Ramon Estruch; Emilio Ros; Ángel M Alonso-Gómez; José Lapetra; Cueto-Galán, Raquel; Fiol, Miquel; et al. (Nutrients, 2021)
This study from the PREDIMED trial examined the relationship between energy balance (deficit or surplus) and mortality risks, including all-cause, cardiovascular, and cancer mortality. It followed 7,119 older participants (mean age 67 years) for a median of 4.8 years. Energy intake was assessed using a food frequency questionnaire, and theoretical energy expenditure (TEE) was estimated based on demographic and physical activity data. Results showed that an energy surplus (intake exceeding estimated needs) was linked to an increased risk of mortality, particularly cardiovascular death. For every 10% surplus, the hazard ratio (HR) for mortality increased by 1.10, and for cardiovascular mortality, by 1.26. Conversely, an energy deficit did not show a protective effect on mortality. Additionally, increments in energy intake over time correlated with a higher risk of all-cause mortality, but reductions in intake did not decrease mortality risk. The study concludes that in older adults following a Mediterranean diet, an energy surplus or increases in energy intake are associated with higher mortality risks, especially cardiovascular. Conversely, energy deficits or reduced intake do not lower mortality risks.
Keywords: Mortalidad; Ejercicio físico; Energy balance; Epidemiology